Migración, economía campesina y ciclo de desarrollo doméstico. Discusiones y estudios recientes - Arias, Patricia (El Colegio de México A.C., 2013)
Based on a review of recent studies conducted in various rural communities in the new migration regions, this article critically reviews two interpretations of rural family studies: the peasant economy as a production-consumption unit and the household development cycle. In the current conditions, internal and international migration play a key role in rural communities. Many studies have shown the willingness of women to leave home and join migratory flows for personal reasons, or due to specific situations and demands. Their departure has contributed to the breakdown of the traditional systems of organization and reproduction of the peasant family. Feminists, and subsequently studies with a gender perspective, criticized the view that rural families were production-consumption units where decisions corresponded to a model of family strategies for survival and reproduction (Hondagneu-Sotelo, 2007; Wolf , 1990). That model favored homogeneity, collectivity, solidarity and consensus, in other words, it assumed that households had no conflicts or tensions when it came to making decisions that involved everyone (Ariza, 2007). The family was a “moral economic unit” based on the principles of “reciprocity, consensus and altruism” (Grasmuck and Pessar, 1991). Studies from a gender perspective pointed out that there were power relations in families based on a hierarchical, unequal distribution of rights, resources and authority that particularly affected women (Ariza, 2007; González Montes, 2002; Hondagneu-Sotelo, 2007; Wolf, 1990). This criticism reached migration studies: migration was not an exclusively male phenomenon; women migrants were not appendages of male migration and their displacement could be based on personal motivation (Ariza, 2007; Hondagneu-Sotelo, 2007).